Does fast running limit numerical variability of the vertebral column in rabbits and hares (Leporidae: Lagomorpha)? - Megu Gunji; Nuttakorn Taewcharoen; Fumio Yamada; Emma Sherratt (Royal Society Open Science)
In mammalian vertebral columns, locomotive ability is expected to be an evolutionary driver of variation in the number of vertebrae; in species evolved to run fast or have a flexible vertebral column, they generally have limited numerical variation and low occurrence of malformed vertebrae to maintain their running performance. Although this hypothesis is supported among species sharing similar locomotive constraints (e.g. dorsomobile versus dorsostable species), whether it applies at the within-species level is unknown. We test this hypothesis using species of Leporidae (rabbits and hares) with different locomotive abilities: we examined the number of presacral vertebrae and the frequency of abnormalities in 504 specimens from 4 species, representing cursorial, saltatorial and generalist modes. Our results show that the cursorial leporids had the lowest numerical variability and fewest abnormalities within species, although this was not statistically different from saltatorial or generalist species. We also identified 11 conditions of vertebral abnormality previously unexplored and theorize that each may pose different degrees of locomotive impairment and effects on species’ fitness. The lack of statistical support for the hypothesis at a finer phylogenetic level suggests further research is needed to understand whether numerical variability is under stabilizing selection or a developmental response to locomotive constraints in cursorial animals.